Effect of oligothiophene π-bridge length in D-π-A star-shaped small molecules on properties and photovoltaic performance in single-component and bulk heterojunction organic solar cells and photodetectors. (December 2021) - Luponosov, Yuriy N.; Solodukhin, Alexander N.; Mannanov, Artur L.; Savchenko, Petr S.; Raul, Benedito A.L.; Peregudova, Svetlana M.; Surin, Nikolay M.; Bakirov, Artem V.; Shcherbina, Maxim A.; Chvalun, Sergei N.; Pshenichnikov, Maxim S.; Paraschuk, Dmitry Yu; et al.
Abstract: Donor-acceptor molecules with thiophene fragments as the π-bridge represent a promising class of materials for organic photovoltaics especially in single-component (SC) organic solar cells (OSCs) and other related applications. However, the effect of the oligothiophene π-bridge length on physicochemical properties, photophysics, charge transport, and photovoltaic performance of these materials has not been thoroughly addressed. Here, we report on the synthesis and comprehensive investigation of the series of star-shaped donor-acceptor molecules (0T –4T ) with triphenylamine as a donor core linked through an oligothiophene π-bridge of variable length to the terminal hexyl-dicyanovinyl electron-withdrawing groups. We found that variation of the π-bridge length from 0 to 4 thiophene units strongly impacts their properties such as the solubility, highest occupied molecular orbital energy, optical absorption and photophysics, film morphology, phase behavior, and molecular packing as well as the charge carrier mobility. The performance of the SC and bulk heterojunction OSCs and photodetectors is comprehensively studied and compared. The results obtained provide insight into how to fine-tune and predict properties and photovoltaic performance of small molecules for organic solar cells and photodetectors. Graphical abstract: Image 1 Highlights: A series of star-shaped molecules with various oligothiophene π-bridge length (0T–4T) is synthesized and characterized. The π-bridge length impacts solubility, photophysics, bandgap, crystallinity, charge carrier mobility, and OSC perfomance. 1T–4T films show relatively balanced ambipolar charge transport and work in organic solar cells with high V oc (up to 1.14 eV). PCE of single-component OSCs increases with elongation of the π-bridge from 0.06% to the remarkable 1.1%. Free charges result from dissociation of charge-transfer excitons, and charge generation follows Onsager's model.